(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to examine the role of Management Information Systems (MIS) in enhancing cybersecurity and data protection within oil companies, with a focus on Mellitah Oil & Gas Company. The main challenge lies in strengthening cybersecurity due to the increasing reliance on digital systems, as cyberattacks pose a significant threat to the confidentiality and integrity of data. The study uses a descriptive-analytical approach, exploring how MIS can be integrated with cybersecurity technologies to protect data and enhance preventive measures against cyber risks. The goal of the study is to provide effective solutions to enhance cybersecurity within oil companies and achieve a higher level of protection against increasing electronic threats. Regarding the statistical aspect, a questionnaire was used as the primary tool to collect data from employees at Mellitah Oil & Gas. The aim was to evaluate the current state of MIS and its contribution to enhancing cybersecurity and data protection within the company. The researcher utilized SPSS statistical software to analyze the data, using both descriptive and analytical statistical methods to extract results. The results revealed a positive correlation between Management Information Systems and improved cybersecurity at Mellitah Oil & Gas, as these systems contribute to increasing security and protecting sensitive data. Some cybersecurity challenges facing the company were also identified, emphasizing the importance of improving security procedures and training employees on best security practices. Based on the statistical analysis, practical recommendations were presented to enhance protection measures and strengthen cybersecurity within the company.